If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + -8x + 7 = x + -8 + 15 Reorder the terms: 7 + 5x + -8x = x + -8 + 15 Combine like terms: 5x + -8x = -3x 7 + -3x = x + -8 + 15 Reorder the terms: 7 + -3x = -8 + 15 + x Combine like terms: -8 + 15 = 7 7 + -3x = 7 + x Add '-7' to each side of the equation. 7 + -7 + -3x = 7 + -7 + x Combine like terms: 7 + -7 = 0 0 + -3x = 7 + -7 + x -3x = 7 + -7 + x Combine like terms: 7 + -7 = 0 -3x = 0 + x -3x = x Solving -3x = x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. -3x + -1x = x + -1x Combine like terms: -3x + -1x = -4x -4x = x + -1x Combine like terms: x + -1x = 0 -4x = 0 Divide each side by '-4'. x = 0 Simplifying x = 0
| 34.8k+.2(1k-4)=1.2-9(2-3k) | | -10(x-5)-8=72 | | 4x-20=6x+14 | | 4w-2+2(w-1)=-38 | | -7k-17=-9k-17 | | 3p+6p-q-3q= | | -7+8r=-5r | | 7+x^3=0 | | 29x-29=57x-85 | | 2(k-6)=4k+2 | | 4.3V-6=8T | | -5p+1=75 | | -10p=30 | | (7x+8)(3x-4)=0 | | 3[2x+5]=9x-6 | | 2x+18=-6x+13 | | -2(3w+4)=3w-5 | | 4(5x+2)+4x+2x+5=403 | | 8(x-9)(2x+9)=0 | | -3(5x-7)= | | 56+80=12+8 | | 20-7y=10 | | 6r=-18 | | 6x-(2x+3)=9 | | 28-.3y=.7-12 | | 91=(99+86+76+95+x)/5 | | (3x-5)(3x-5)=25 | | x^2+3*x-5=175 | | 2x=-34 | | 2+(x+1)+5x=4 | | 7(A-6)= | | 7(X+4)=4X+3 |